AI for Social Good: Leveraging Artificial Intelligence for Community Development - Hasas, Ansarullah; Hakimi, Musawer; Shahidzay, Amir Kror; Fazil, Abdul Wajid (PT. Riset Press International, 2024)
This research explores the impact of Artificial Intelligence (AI) on community development, spanning healthcare, education, environmental sustainability, and community empowerment. The purpose of this study is to comprehensively analyze the perceptions and experiences of participants in underserved communities regarding AI applications. Employing a mixed-methods approach, quantitative surveys provide statistical insights, complemented by qualitative narratives to capture nuanced perspectives. The methodology involves surveying 120 participants from diverse occupations and age groups, utilizing Likert scales and regression analysis. The results reveal a positive perception of AI across domains, emphasizing its potential for positive societal outcomes. Noteworthy is the statistical significance of AI's impact on healthcare, education, and environmental sustainability. The inclusion of qualitative narratives enriches the findings, providing depth to statistical measures. The novelty of this study lies in its holistic exploration of AI's impact on community development, integrating quantitative and qualitative dimensions. The research contributes to the field by providing nuanced insights into the multifaceted aspects of AI in community contexts. In conclusion, this study underscores the need for responsible AI deployment, aligning with community values, as communities navigate the evolving technological landscape.